Pengaruh Pembiayaan KUR Terhadap Perkembangan Usaha Mikro Kecil Menengah (UMKM) Jelutung Pada Bank BSI KC Gatot Subroto Kota Jambi - Zamharir Zamharir; A.Tarmizi M.H.I; M. Taufik Ridho (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This thesis is a study that examines the influence of People's Business Credit (KUR) on the development of Jelutung micro, small and medium enterprises (MSMEs) at Bank BSI Kc Gatot Subroto, Jambi City. The purpose of this thesis is to be able to find out the effect of people's business credit (KUR) on the development of MSME businesses and to be able to find out the amount of contributions made by KUR to the business development of customers of Bank Syariah Indonesia Kc Gatot Subroto Jambi City.In this study using quantitative methods with data collection techniques namely observation, questionnaires and documentation. Which is the questionnaire itself as an instrument in collecting data. Then a validity test and reliability test were carried out to ensure the accuracy of each question item in the questionnaire to be used in collecting data. After that, a classic assumption test was carried out to ensure the soundness of the data and a hypothesis test in the form of a (t) test, simple linear regression test and test for the coefficient of determination (R2).The results of this study are as follows: (1) People's Business Credit (KUR) has a significant and positive effect on customer business development as evidenced by the significance of KUR of 1.68107 > 0.05 and also the value of the simple regression results which obtains a value of 0.554 which indicates a positive number so that the influence that KUR has is good or positive on the development of the customer's business. (2) The contribution made by KUR to the development of the customer's business is 0.47.8 or 47.8% and the remaining is 0.552. Or 52.2% is influenced by variables or other factors not mentioned in this study.